Pelaksanaan Fungsi International Labour Organization (ILO) Melalui Better Work Bangladesh dalam Perlindungan Pekerja Perempuan - Zahra Wiranda; Anita Afriani Sinulingga; Diah Anggraini Austin (Hubungan Internasional Universitas Andalas, 2026)
This research aims to analyze the functions of the international organizations, specifically the International Labour Organization (ILO) through the Better Work Bangladesh (BWB) program in promoting decent work for female workers in Bangladesh’s garment industry. Despite being the world’s second-largest garment exporter with a predominantly female workforce, the fulfillment of workers’ rights remains inadequate. Using the framework of International Governmental Organizations (IGOs) proposed by Karns, Mingst, and Stiles, the research examines how BWB addresses gender discrimination, enhances training opportunities, and fosters inclusive workplaces. Employing a qualitative descriptive case study, the study relies on document analysis of annual reports, ILO publications, and related sources. The findings indicate that BWB has improved compliance with labor standards, particularly regarding working hours, wages, non-discrimination, and protection for women workers. Initiatives such as GEAR and Mothers@Work, implemented in collaboration with the IFC and national stakeholders, further strengthened gender-responsive labor governance. The study concludes that BWB serves as a collaborative platform linking international and domestic actors in advancing decent work and gender equality in Bangladesh’s garment sector.